DEVELOPING COURSE BOOK IN TEACHING PRONUNCIATION - Trisnendri Syahrizal; Ula Nisa El Fauziah; Lilis Suryani (Jurnal Ilmiah P2M STKIP Siliwangi, 2020)
Abstract Pronunciation as one of the speaking element works an important role in students’ speaking. Many research has been conducted in both how to improve students’ pronunciation and developing the theories. As problems, many students faced some difficulties in producing proper English sounds; additionally the teachers also have problems in selecting proper material and exercise for the students. This research attempted to develop a course book in teaching pronunciation that can help the teacher in managing the classroom and support the independent learning process of the students. The Research and Development (R&D) is used as method of the research since this method is very suitable for developing a new product or perfecting an existing product that can be justified. This method is divided into three parts; introductional study, product development, and testing involve validation from experts, and revision. The subject of the research is the second semester students of English education study program of IKIP Siliwangi. The instruments used were observation, interview ,and test validation. The observation used to see the real condition during the implementation of the topics. Interview was conducted to gather the data related with the topic used in the course book in every unit. There were eight topics obtained through the interview. The test is used to validate the eligibility of each topic. From the result, the mean score of content was 79.75, while display was 78.05 and language was 78.86. The researchers conclude that this course book can be used as learning resources in teaching pronunciation.Keywords: course book, pronunciation, R and D  Abstrak Pronunciation adalah salah satu element kemmapuan berbicara yang memiliki peranan penting. Banyak penelitian yang sudah dilakukan pada peningkatan pronunciation siswa dan pengembangan teori. Siswa memiliki masalah dalam memproduksi bunyi dalam Bahasa inggris, selain itu guru juga memiliki masalah dalam menentukan materi dan latihan yang sesuai. Penelitian ini mencoba untuk mengembangkan sebuah bahan ajar dalam pengajaran pronunciation yang dapat membantu guru dalam mengelola kelas dan mendukung proses pembelajaran yang mandiri. Research and development (R and D) digunakan sebagai penelitian karena penelitian ini sangat sesuai untuk mengembangkan sebuah produk baru bahan ajar. Metode ini dibagi menjadi tiga bagian yaitu: studi penndahuluan, pengembangan materi, dan   uji validasi dari para ahli. Subjek penelitian ini adalah mahasiswa semester dua pendidikan Bahasa inggris di IKIP Siliwangi. Instrumen penelitian ini adalah observasi, wawancara,dan tes validasi. Observasi dilakukan untuk mengetahui kondisi lapangan dalam pembelajaran pronunciation. Wawancara digunakan untuk mengumpulkan data sesuai dengan topik bahan ajar. Ada delapan topik dalam buku bahan ajar ini berdasarkan hasil wawancara. Kemudian test validasi dilakukan untuk mengukur bahan ajar yang di hasilkan. Dari hasil penelitian, rata-rata nilai isi buku adalah 79.05, sedangkan tampilan buku adalah 78.05, dan Bahasa adalah 78.86. Peneliti menyimpulkan bahwa buku bahan ajar dapat digunakan sebagai sumber bahan ajar dalam pengajaran pronunciation. Kata Kunci: Pronunciation, bahan ajar, R dan D